Ghoulfriends forever / 1. - Daneshvari, Gitty (Daneshvari, Gitty. Monster High (New York : 2012- ), 2012)
Rochelle Goyle, Venus McFlytrap, and Rebecca Steam become fast friends when they meet on their first day at Monster High, and, when the three discover an evil plot against Monster High, they have to work together to save the school.